Status Keabsahan Salat bagi Penderita Ambeien dalam Perspektif Fikih Ibadah (Studi Komparatif mazhab Malikiyyah dan Syafi'iyyah) - Mizan Hadi Nurhikam; Asri Asri; Muh. Isra Syarif (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine the views of the Mālikiyyah and Shafiʻiyyah schools on the validity of prayer for hemorrhoid sufferers and to find out the similarities and differences between these two schools on the matter. The type of research used is qualitative descriptive research using library research methods and with normative and comparative approach methods. From the results of this study, it was found that the status of the validity of prayer in the Mālikiyyah school was valid because they considered the blood coming out of the rectum not including hadas and the unclean law was excused on emergency grounds. While the Shafiʻiyyah school views hemorrhoid blood as divided into two categories, those that come out of the rectum including hadas so that the prayer is void, then the validity of the prayer is void if the hemorrhoid is internal and valid if the hemorrhoid is externa. The unclean law is forgiven on condition that he must clean every time he wants to pray and must wrap his rectum.